Study of the Impact of Adding Dried Biosolids to Portland-Type Cement when Making Mortars - Hernandez-Garcia, Johan-Felipe; Sánchez-Perdomo, Laura-Julieth; Silva-Vega, Gabriel-Santiago (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This research focuses on the implementation of dried biosolids from the El Salitre wastewater treatment plant in the city of Bogotá in the mixture for the preparation of N-type mortars as a partial replacement for Portland-type cement. To carry out the experimental process, the physical properties of the materials were considered, such as their preparation and mixing, followed by the breaking test, and finally, with the collected data, the optimal percentage of biosolids for a mixture with the minimum compression strength technically required was determined. The results obtained show that the percentage of biosolids included in the mortar mixture is inversely proportional to the strength achieved due to the porous nature of the composition of these materials. Therefore, mixtures where 5% and 10% of the cement was replaced with dried biosolids performed better in the compression tests, even better than the conventional mixture in which these materials are not included. Consequently, these dosages can be adopted in the construction industry as an additive to the typical mortar mixture (1:4), which reduces the unfavorable environmental impact, encourages a circular economy in the industrial process of making mortars, and contributes to the sustainable development for environmental preservation. This makes the use of biosolids attractive for their inclusion as supplementary cementing material in the cement industry.